Research of left ventricular global longitudinal strain using speckle- tracking echocardiography in patients with chronic heart failure - Nguyen, Thi Thuy Hang; Nguyen, Vu Ha Nguyen; Vo, Van Tho (Tạp chí Y Dược Huế, 2025)
Objectives: To evaluate the characteristics of left ventricular global longitudinal strain using speckle tracking echocardiography in heart failure patients and determine the relationships between global longitudinal strain and NYHA, EF, NT proBNP in heart failure disease. Materials and methods: A descriptive and cross-sectional study on 97 patients with HF. The patients were examined and treated at the Hue University of Medicine and Pharmacy Hospital from May 2021 to July 2023. Results: The mean age was 72.08 ± 13.53 years old. The median NT-proBNP value was 1053 (366 - 2795.5) pg/ml. The mean value of EF- Simpson is 45.47 ± 12.87%. The mean GLS (%) value is -13.08 ± 3.36 %. GLS (%) and GLSR (1/s) progressively decreased according to NYHA heart failure level and EF (p < 0.05). NT-proBNP has positive linear regression correlations with GLS (%) and GLSR (1/s) (r1 = 0.893, r2 = 0.736, p < 0.01), but has a negative linear regression correlation with EF-Simpson (%) (r3 = -0.785, p < 0.01). GLS (%) also has a strong negative linear regression correlation with EF-Simpson (%) (r = -0.772, p < 0.01, y = 6.42 - 2.99 a x). Conclusion: Both GLS (%) and GLSR (1/s) have a relationship with the two classic prognostic factors, including NYHA classification and LVEF. The GLS (%) index has a stronger linear correlation with NT-proBNP when compared to EF-Simpson.